New measurement technique for characterizing small extraterrestrial materials by X‐ray diffraction using the Gandolfi attachment - Imae, Naoya; Kimura, Makoto (Meteoritics & Planetary Science, 2020)
Abstract Identification and characterization of small extraterrestrial samples, such as small Antarctic meteorites <~1 cm, require the development of convenient laboratory‐based nondestructive analytical techniques using X‐ray diffraction (XRD). We explore the characterization criteria using an X‐ray diffractometer with a Gandolfi attachment using sub‐mm small fragments and powder aggregates for various kinds of stony meteorites and develop a new analytical technique. We primarily focus on olivine and pyroxene because they are the most abundant and important minerals for stony meteorite classification. A new calibration is performed to estimate the FeO content of the olivine in unequilibrated ordinary chondrites, which is useful for determining the meteorite chemical group irrespective of powder aggregate diameter but dependent on fragment grain diameter. This is because X‐ray intensity absorption is more effective for grains than for powders. Clinoenstatite (Cen) and orthoenstatite (Oen) were distinguished using the presence or absence of the isolated Oen 511 index peak. The method is also applied to other stony meteorites including carbonaceous chondrites and achondrites. The XRD results are consistent with studies based on polished sections involving textural observations by scanning microscope and chemical compositions of the constituent minerals. The new measurement technique presented here is convenient because of its use in air by the laboratory‐based X‐ray diffractometer, which makes it useful for the initial analyses of restricted extraterrestrial sample characterization.